Engaging ICT-Supported Learning Activities to Achieve ELT Curriculum Goals: A Qualitative Case Study - Marsevani, Maya; Evans, Johnathan; Rumianti, Melisa Ayu; Nugraha, Hendra (Journey: Journal of English Language and Pedagogy, 2026)
This case study examined how English teachers planned and implemented ICT-supported learning activities to achieve the objectives of the Merdeka Curriculum in English Language Teaching. The study involved three advanced English teachers from three senior high schools in Batam, with one teacher representing each school. Participants were selected through purposive sampling based on their experience in implementing the curriculum and integrating digital tools into English instruction. Data were collected through three classroom observations, semi-structured interviews consisting of 33 open-ended questions, and researchers’ field notes. The data were analyzed using the interactive model of Miles, Huberman, and Saldaña, which includes data condensation, data display, and conclusion drawing and verification. The findings showed that the teachers used Canva, YouTube, Quizizz, Google Forms, and Microsoft PowerPoint to support communication, collaboration, creativity, engagement, and differentiated instruction. However, ICT implementation remained limited because of unstable internet connections, inadequate classroom facilities, unequal access to digital devices, and insufficient professional training. Consequently, textbook-based instruction remained prominent. These findings reveal a gap between the progressive expectations of the Merdeka Curriculum and classroom realities. Schools should therefore improve digital infrastructure and provide professional development focused on technological, pedagogical, and content knowledge for meaningful and sustainable ICT integration.